Quantitative analysis of serum cell-free DNA as a predictive and prognostic marker in breast cancer patients - Sultana, Gazi Nurun Nahar; Akter, Ferdowsi; Israfil, S. M. Hasan; Ray, Utpal Chandra; Jahan, Rumana Akther; Ali, Mohammad Shawkat; Din, Salim Al; Rahman, Shafiqur; Halim, Rezaul; Alam, Mohammad Sahajadul (Frontiers in Oncology, 2023)
Abstract The prognosis of breast cancer may be predicted using circulating cell-free DNA (cfDNA), a non-invasive diagnosis technique. This study aimed to determine the most sensitive and effective method for detecting changes in cfDNA levels and for using cfDNA as a diagnostic and prognostic marker of breast cancer. This research suggests that the most successful way to measure the amount of cfDNA described decades ago could be used as a "liquid biopsy" to track cancer in real time. The potential function of serum cfDNA levels as a marker for early breast cancer diagnosis was investigated using UV spectrophotometric, fluorometric, and real-time qPCR assays. The RT-qPCR (ALU115) method produced the most statistically significant results (p=0.000). At the threshold concentration of 395.65 ng/ml of cfDNA, the ROC curve reflects the maximum AUC= 0.7607, with a sensitivity of 0.65 and specificity of 0.80. For a preliminary assessment of total circulating cfDNA, a combination of all of the above techniques will be most efficacious. Based on our results, we conclude that the RT-qPCR technique combined with fluorometric measurement can identify a statistically significant difference in cfDNA levels between cohorts of breast cancer patients and healthy controls.